The Distance Learning as the Reason of Child Abuse under Pandemic of COVID-19 - Afanasiev, Dmytro; Oros, Oleksandra (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Researches suggest that child abuse is related to a previous history of violence within the family setting and the evolution of the learning process. The current study was aimed to investigate the exposure of child abuse in the case of distance learning and its relationship to some variables of the social-cognitive processing among parents who potentially assaulted their children. The survey research method was applied. The questionnaire consisted of three blocks of questions: socio-demographic block, parents’ impressions of distance learning at school, violence, and parents’ aggression towards children. The sample included 308 primary school children’s parents from the Zakarpatska region (Ukraine). Results show that parents’ reaction to learning difficulties is not always constructive because most stressful situations provoke verbal aggression and physical violence towards the child. Distance learning and related difficulties have become a major factor in violent and aggressive behavior towards children during quarantine. Most parents who allowed maltreatment toward their children before pandemic COVID-19 also demonstrated it during distance learning. Our study found a link between parents’ use of physical violence and verbal aggression with the following variables: duration of lockdown, the function of the teacher in distance learning, parents’ assessment of the process and learning outcome, qualitative changes in the relationship between parents and children during quarantine. The study of violent situations against children during distance learning will provide an opportunity to develop effective preventive and corrective measures. The process of informing about situations of violence against children can have a psychoprophylactic effect